Startups and Effective Corporate Governance Models Proposed by the RA Legislation - Avetisyan, Vahram (Bulletin of Yerevan University C: Jurisprudence, 2021)
The article is devoted to identifying problems and presenting relevant solutions related to the definition of control systems, therole of a shareholder agreement in corporate governance, corporate conflicts, selfdefense of corporate rights, the choice of a corporate governance model for a company,as well as the choice of the most preferred form of legal entity for start-up companiesoffered by the RA legislation.
Keywords: startups; shareholder agreement; corporate governance; classes of ordinary shares; corporate conflicts; self-protection of rights; governance models